Diagnosis of bursal‐side partial‐thickness rotator cuff tears - Xiao, Jian (Orthop Surg, 2010)
Objective:  To study the clinical features and diagnosis of bursal‐side partial‐thickness rotator cuff tears. Methods:  From August 1999 to June 2006, 38 patients with bursal‐side partial‐thickness rotator cuff tear were evaluated. Twenty‐eight men and ten women of average age 45.7 years (range, 18–69 years) with 11 left and 27 right shoulders were studied. According to the Ellman classification, 6 cases were classified as grade I, 7 as II and 25 as III. Physical and X‐ray examination, including anteroposterior and supraspinatus outlet views, were performed on both shoulders of all patients. Ultrasonography and MR examination were performed in 27 and 35 patients, respectively. Thirteen patients underwent arthroscopic subacromial decompression and debridement of the rotator cuff. Twenty five patients underwent arthroscopic or mini‐open subacromial decompression and rotator cuff repair. Results:  All patients had shoulder pain, with 18 cases of night pain. No statistical difference in the incidence of night pain was found between the three groups. Strength of forward flexion and abduction of the affected shoulder was decreased in 25 patients. The Neer impingement sign was found in 35 cases (92.1%), Hawkins impingement sign in 27 (71.1%), tenderness of the greater tuberosity in 34 (89.5%), painful arc in 26 (68.4%), and traction test in 26 (68.4%). The positive rates for ultrasonography and MR were 48.1% and 74.3%, respectively. Conclusions:  Long‐standing motion pain, impingement sign, painful arc, lock and crepitus in the subacromial space are suggestive of bursal‐side tears. MRI is much more accurate than ultrasonography. Fat‐suppressed T2‐weighted images must be included. Arthroscopy is still the gold standard for making the diagnosis.